TRENDS AND INNOVATIONS IN THE PET FOOD MARKET - Baroncello, Sheila; Gelinski, Jane Mary L. N.; Caliari, Vinícius (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Studies show that Brazil in the world ranking is the second country with the largest population of domestic animals, with the front only the US. These animals, which usually occupied a decorative space, were valued as a company and considered an integral part of the family.It is estimated that 59% of Brazilian households have some pets, spending an average of R $ 390,00 on products and services (pharmaceuticals, vaccines, beautification and accessories). In this survey we evaluate the current situation of the pet market, trends and innovations, especially on snacks/foods with high added value. In this research we have compiled national and international circulation periodicals for the last five years (2012-2017). It was found that the world market grew at an annual average of 17%, earning around US $ 1.5 billion since the year 95. The Brazilian market in 2014 reached R $ 16 billion, placing the country in the third position in the ranking world. The food segment is the main representative of the sector, with 67% of revenues. It is verified that the trend of the sector is directed towards health and animal welfare focused on health and practicality. It is generally seen that the market is susceptible to changing societal patterns and demands impose imposed by consumers, and to achieve competitive advantage must constantly be on the side of innovative technologie.